2012
DOI: 10.1080/00223891.2012.700466
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of the Mini-IPIP in a Large, Nationally Representative Sample of Young Adults

Abstract: Drawing on a large, nationally representative sample of young adults (the National Longitudinal Study of Adolescent Health; N = 15,701; M age = 29.10), we evaluated the psychometric properties of the Mini-IPIP, a 20-item inventory designed to concisely assess the 5 factors of personality. The results suggest that the Mini-IPIP has a 5-factor structure; most of the scales have acceptable reliability; all the scales have partial or full metric invariance; and the scales exhibit some degree of criterion validity.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
87
0
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(117 citation statements)
references
References 45 publications
15
87
0
8
Order By: Relevance
“…Conscientiousness,N euroticism, Intellect/imagination and Sensation Seeking), indicating low reliability; similar alphacoefficients were reported in previous studies that investigated the psychometric properties of the Mini-IPIP and the AISS in adolescent samples (Baldasaro, Shanahan, &Bauer, 2013;Roth &Herzberg, 2004). As for the AISS, the proposed distinction in two latent factors(i.e.…”
supporting
confidence: 51%
“…Conscientiousness,N euroticism, Intellect/imagination and Sensation Seeking), indicating low reliability; similar alphacoefficients were reported in previous studies that investigated the psychometric properties of the Mini-IPIP and the AISS in adolescent samples (Baldasaro, Shanahan, &Bauer, 2013;Roth &Herzberg, 2004). As for the AISS, the proposed distinction in two latent factors(i.e.…”
supporting
confidence: 51%
“…Studies have indicated sound psychometrics for the 20-item short version of the Big Five. For example, Baldasaro, Shanahan, and Bauer (2013) (Tabachnick & Fidel, 2014), provided the results are treated with caution. (Ryff, 1989;Ryff & Keyes, 1995).…”
Section: Methodsmentioning
confidence: 99%
“…Statements are rated on a 5-point Likert scale ranging from "1-Very Inaccurate" to "5 -Very Accurate", with a mid-point of "3 -Neither agree nor disagree). The five-factor structure of the Mini-IPIP has been supported across several studies and has adequate internal reliability for all sub-scales (α's > .60) [49,50].…”
Section: Psychological Characteristicsmentioning
confidence: 94%